2019
DOI: 10.1038/s41598-018-37064-x
|View full text |Cite
|
Sign up to set email alerts
|

Three Prime Repair Exonuclease 1 (TREX1) expression correlates with cervical cancer cells growth in vitro and disease progression in vivo

Abstract: Alterations in specific DNA damage repair mechanisms in the presence of human papillomavirus (HPV) infection have been described in different experimental models. However, the global effect of HPV on the expression of genes involved in these pathways has not been analyzed in detail. In the present study, we compared the expression profile of 135 genes involved in DNA damage repair among primary human keratinocytes (PHK), HPV-positive (SiHa and HeLa) and HPV-negative (C33A) cervical cancer derived cell lines. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
(36 reference statements)
1
13
0
Order By: Relevance
“…It has been widely reported that HPV oncoproteins promote DNA damage and OS involved in cancer initiation and progression [ 31 , 32 , 33 ]. However, the role of E7 oncoprotein in oral cancer progression has not been sufficiently addressed, although it is critical for immortalization and cell transformation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that HPV oncoproteins promote DNA damage and OS involved in cancer initiation and progression [ 31 , 32 , 33 ]. However, the role of E7 oncoprotein in oral cancer progression has not been sufficiently addressed, although it is critical for immortalization and cell transformation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study proposed E7 as the oncoprotein which hampers the DNA damage response to DSBs by interacting with the E3 ligase RNF168 involved in DNA DSB repair 62 . It has also been observed that expression of an exonuclease with a proofreading function, Three prime repair exonuclease 1 (TREX1), is upregulated exclusively in HPV-transformed primary keratinocytes expressing HPV 16 E6 and E7 77 . Downregulation of TREX1 resulted in inhibition of cell growth, which was associated with p53 upregulation.…”
Section: Ongoing Clinical Trials On Treatment For Hpv-related Cancersmentioning
confidence: 99%
“…Recently, several studies have reported the association between the TREX1 and tumorigenesis. Prati et al (6) indicated that TREX1 upregulation was an important factor for the growth of cervical tumor cells and may contribute to tumor progression. Also, malfunction of DNA mismatch repair genes, including TREX1, has been reported to be associated with a risk of gastric cancer by causing microsatellite instability (5).…”
Section: Discussionmentioning
confidence: 99%
“…Vanpouille-Box et al (13) identified TREX1 as a key determinant for the limited immunogenicity of cancer cells responding to single high-dose radiation. The role of TREX1 in carcinogenesis is still unclear, but recent studies have shown that the alteration of TREX1, which is essential for DNA damage repair and elimination of cytoplasmic DNA, consequently preventing the activation of innate immune mechanisms, may lead to cancer development (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation